On the Covariance of Moore-Penrose Inverses in Rings with Involution - Hesam Mahzoon (Abstract and Applied Analysis)
We consider the so-called covariance set of Moore-Penrose inverses in rings with an involution. We deduce some new results concerning covariance set. We will show that if a is a regular element in a C∗-algebra, then the covariance set of a is closed in the set of invertible elements (with relative topology) of C∗-algebra and is a cone in the C∗-algebra.